Gas to Wire (GTW) Model in Brazil: Challenges and Possibilities - Souza, Leonardo; Santos, Rodrigo; Miranda, Daniel (International Journal of Petroleum Technology, 2022)
The expansion of natural gas production in Brazil presents some obstacles, the main one being the reduced volume of investments in expanding the transportation, distribution, and commercialization of natural gas produced offshore and onshore in the country. If, on the one hand, the lack of investments in infrastructure for the flow of natural gas produced in the country prevents the expansion of natural gas production in the onshore basins, the transformation of electric power near the reservoirs of natural gas has enabled the viability of projects for exploration and production of natural gas in the Brazilian onshore basins. A review of literature and analysis of secondary data allows the study of technical, legal, and economic factors that enable the implementation of a reservoir to wire projects, from the production of natural gas in the onshore basins of Brazil, aiming at the supply of electric power to the National Electric System. This way, natural gas changes its condition as a complementary energy source, together with the National Electricity System, to exercise the function of a basic energy source for parts of the national system.